Towards a hermeneutic understanding of literacy identity : four case studies - Ó Séaghdha, Finín (Trinity College (Dublin, Ireland). School of Education, 2014)
Rather than conceive of literacy simply as a set of decoding and comprehension skills, some scholars now consider literacy to be tightly bound up with individual's evolving sense of identity. While some studies have explored at the development of student literacy identity, more research is needed into the role that teachers play in that development. 'Identity' according to Bauman, 'is the loudest talk in town; the burning issue on everyone's mind and tongue' (Bauman, 2004:17).
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin